Rancang Desain User Interface Digital Platform Logistik PT Pos Indonesia - Sulistiyaningsih, Febriani; Fayaqun, Reza; Numang, Irpan (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
PT Pos Indonesia is the oldest Badan Usaha Milik Negara (BUMN) in Indonesia. PT Pos Indonesia is known as a state-owned company operating in the logistics sector. This is because the core business of PT Pos Indonesia is a service for sending goods from one place to another, apart from selling stamps, sending money and so on. The development of technology and information has really helped the business processes at PT Pos Indonesia by providing various applications that are used, but the many applications available are not all integrated with one another. So in this research, a logistics platform design plan was carried out which will later integrate existing applications or systems at PT Pos Indonesia. This design will be in the form of a user interface, which is the design of the system interface. This research uses the System Development Life Cycle (SDLC) or waterfall method which has clear stages.